STRATEGI PROMOSI DALAM MENINGKATKAN VOLUME PEJUALAN KOPI (STUDI KASUS DI KOPI BABAH KACAMATA) - Valentina Apriani; Lasmono Tri Sunaryanto (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2022)
Babah Kacamata Coffee is an individual bussiness that produces coffee beans into coffee powder. The production of their coffee powder is more than the demand for it. So, Babah Kacamata Coffee wants to increase the volume of its sales, but there is trouble in its marketing. The marketing that has been done before was by advertising was not maximal because the information about the product was not completed. As the promotion was not effective, the information about the product was not shared enough with the consumer. So, there must be an identification strategy for the promotion of Babah Kacamata Coffee to increase the volume of their sales. The purpose of this research: 1) To find the strengths, the weaknesses, opportunities, and threats of Babah Kacamata Coffee, and 2) To find the promotion strategy that will increase the volume of their sales. This research is carried out with the purpose ( purposive) of the consideration of Babah Kacamata Coffee which has been a long time producing the coffee beans in Salatiga even though its market is still local. The type of this research is descriptive qualitative with an interview method to find the strengths, weaknesses, opportunities, and threats( SWOT) of Babah Kacamata Coffee. The result of this research shows that the strengths, weaknesses, opportunities, and threats related to the promotion strategy. The factor from SWOT analysis is that to form the new strategy to increase the volume of their sales from the promotion of the development and the implementation of the promotion to overcome weaknesses and threats also take advantage of opportunities through existing strengths.